Different Paths of Development of Two Information Systems Communities: A Comparative Study Based on Peer Interviews - Frank, Ulrich; Schauer, Carola; Wigand, Rolf (Communications of the AIS, 2008)
Information Systems (IS) is not a homogeneous discipline. Rather, it is comprised of various communities that are characterized by different perspectives and methods. With regard to the ongoing discussion about the profile of the discipline, this is a remarkable phenomenon. More specifically, it recommends analyzing the characteristic features of the various IS communities and explaining the diverse paths of development they took. Furthermore, it implies the question whether—and how—the current diversity could be overcome in order to foster a more focused competition as well as a more coherent presentation of research results on an international scale. This article contributes to such an investigation. It is focused on a comparison of the international English-speaking community predominantly (in particular in its early days) shaped by North- American IS researchers, which plays a leading role in the international scene, and the IS discipline in German-speaking countries (”Wirtschaftsinformatik” or WI, in Austria, Germany, and Switzerland), which constitutes the largest IS community outside North America that maintains its own approach. The focus of this article is mainly on describing the communities’ characteristics as the outcome of a social construction that is chiefly influenced by those individuals who participated in this construction. Against this background, eight scholars from North America and six scholars from German-speaking countries were interviewed at length. All were chosen as witnesses of and important contributors to the development of their discipline. As a result of this reconstruction, the article presents a rich picture of the communities’ history and characteristics as experienced and reported by the interviewees. The results obtained from this project indicate that neither of the two conceptions (IS or WI) can serve as an ideal model. Instead, a more intensive international exchange among the various research communities, including the Scandinavian and British scholars, should contribute to further develop the field into a more mature and satisfactory state.